Associations of adherence to the DASH diet and the Mediterranean diet with chronic obstructive pulmonary disease among US adults - Wen, Jingli; Gu, Shujun; Wang, Xinyu; Qi, Xu (Frontiers in Nutrition, 2023)
Background:The Dietary Approaches to Stop Hypertension (DASH) and the Mediterranean diet are associated with reduced cardiovascular, tumor, and diabetes risk, but the effect on chronic obstructive pulmonary disease (COPD) is uncertain. Objective:To investigate the association of the DASH diet and the Mediterranean diet with the risk of COPD in American adults. Methods:The scores of healthy eating patterns (the DASH diet and the Mediterranean diet) were derived from a 24-hour dietary recall interview (individual food and total nutrient data from NHANES and food pattern equivalents data from the United States Department of Agriculture (USDA)). The primary outcome was the prevalence of COPD. COPD was defined based on participants self-reported whether or not a doctor or health professional had diagnosed chronic bronchitis or emphysema. Secondary outcomes were lung function and respiratory symptoms. All analyses were adjusted for demographics and standard COPD risk factors (primary tobacco exposure, secondhand smoke exposure and asthma). RESULTS:This study included 2488 COPD participants and 25607 non-COPD participants. We found that a higher DASH diet score was associated with a lower risk of COPD (odds ratio [OR]: 0.83; 95% confidence interval [CI]: 0.71-0.97; P = 0.021). This association persisted in several subgroups (men [OR: 0.73; 95% CI: 0.58-0.93; P = 0.010], relatively young [OR:0.74; 95% CI: 0.55-1.01; P = 0.050] and smoker [OR: 0.82; 95% CI: 0.67-0.99; P = 0.038]). In contrast, the Mediterranean diet score was not significantly associated with COPD prevalence in this large cross-sectional analysis representative of the US adult population (OR: 1.03; 95% CI: 0.88-1.20; P=0.697). In addition, we found a correlation between DASH diet adherence and lung function (β: -0.01; 95% CI: -0.01 to 0.00; P=0.003 [FEV1: FVC]) or respiratory symptoms (OR: 0.80; 95% CI: 0.73-0.89; P <.001 [dyspnea]; OR: 0.80; 95% CI: 0.70-0.91; P=0.002[cough]; OR:0.86; 95% CI: 0.74-0.99; P = 0.042 [expectoration]), especially in non-COPD populations. Conclusions:A higher DASH diet score was associated with improved COPD prevalence, lung function and respiratory symptoms. This new finding supports the importance of diet in the pathogenesis of COPD and expands the scope of the association of the DASH diet score with major chronic diseases.